Professores de música em escolas particulares em Santa Maria - RS: um estudo a partir de diários de aulas - Raposo, Mariane Martins (2014)
This research aims to observe the ways of becoming music teachers of professionals in private schools at Santa Maria, in Rio Grande do Sul. This process proceed by a qualitative research methodology, in a (auto)biographic way, by diary s class. The research group counted on four music teachers, who had written about their daily class practices, following a methodology based on Zabalza (2004). These diaries has been shared among this teachers, and each one wrote about their professional acting. Beyond the analyses of the description of theirselfes, was searched the applications and developments of care of self structures. The self care concept came from the study of Foucault (2012), Filho (2011) and Ribeiro (2013). The lathing of the methodology and the care of self concept with the appreciation about the scenes of education and music education in actuality alowed view the impressions, opinions and reflective compositions of these teachers and how the associations between their narratives allowed these professionals to create ways of organizing their professional practices becoming them active agents of their personal stories.